ESTATUS Y CONCEPTO DE LO POÉTICO EN EL RAP, EL TRAP Y LA MÚSICA URBANA. EL CONTEXTO ESPAÑOL - Luque Amo, Álvaro (Signa (Madrid, Spain), 2024)
This article studies the musical genre of rap and its current derivations, trap, and urban music, in order to analyse both the concept and the status of the existing poetic genre among Spanish artists who can be ascribed to these modalities. The chosen corpus is divided into two time periods: on the one hand, we study the rap that began to be practised in Spain in the 1990s and developed in the first decade of the 21 st century; on the other, we analyse two new modalities that appeared or developed after 2011, namely trap and urban music. Thanks to this division, these pages show how the artists' conception of the poetic changes from one period to the next. This helps to understand both the idiosyncrasies of these genres and the differences that exist between them, always in the Spanish context, as well as the link that can be found in the literary genre of poetry and current music.